Counter-Extremism, Fundamental Values and the Betrayal of Liberal Democratic Constitutionalism. Issue 2 (1st May 2018) - Rivers, Julian
Abstract : Over the course of the last three years, British Government counter-terrorism policy has shifted significantly to embrace "counter-extremism." This is justified not only in terms of addressing the underlying causes of terrorism, but also in its own right as addressing the "harm" of extremism. These proposals raise fundamental questions about the limits of religious and other civil liberties. However, the problem of extremism is not new. The German public intellectual and constitutional lawyer Ernst-Wolfgang Böckenförde reflected extensively on the same problem in the context of German responses to left-wing radicalism in the mid-1970s. His work touched on both concrete legal problems as well as fundamental philosophical assumptions about the nature, characteristics, and limits of the liberal democratic constitutional state. In this article, I seek to retrieve his ideas and arguments for the current British context. I argue that the current discourse of extremism and fundamental British values risks being used as a vehicle for promoting a "progressive" public ideology of individual self-creation. This fails to take moral and religious diversity seriously, and its implementation betrays the foundations of the liberal democratic constitution. It provides striking confirmation of Böckenförde's thesis that the liberal state is perennially prone to a totalitarian tendency to seek to generate its own distinctive ethical community. As Böckenförde recognized, what is needed instead is the recovery of a thin common morality of civic loyalty as shown pre-eminently in obedience to law.